Investment Activity of Natural Persons: Russian Experience of Tax Stimulation - Smirnova, Elena Evgenievna (International Journal of Economics and Financial Issues, 2015)
This article examines the problems of the defining investment activity of natural persons in the Russian Federation and in the world community and provides offers on its stimulation. In modern Russia, much attention is paid to the taxation policy in the line of stimulation of enterprises investment activity. Thus, an extremely important task is that of state stimulation of investments in the creation and development of the profitable enterprises. In the article, we consider the issue of creating a favorable taxation climate for innovation activity. The taxation system of the Russian Federation should provide the possibility for the creation of a demand for investments in new technologies, equipment modernization and introduction of research results. Human capital is the main factor of economic development. Nowadays, negative trends exist in the development of human potential, characterized by a low quality and decrease of the social education services accessibility level. Keywords: personal income tax; investment activity; innovative development; economy modernization; tax incentives and preferences; tax instruments. JEL Classifications: F21; H21; H24